Application of newly proposed hardening laws for structural steel rods - Nguyen, Van Nam; Doan, Duy Triet; Doan, Nhat-Phi (Vietnam Journal of Mechanics, 2024)
In civil engineering, distinct mechanical properties and behaviors of structural steel rods necessitate a novel approach to material modeling. This study extends the application of recently proposed strain-hardening laws, originally developed for automotive sheet metals, to several structural steel rods (CB240-T and CB300-T). Standard uniaxial tensile tests are conducted for each examined material to obtain experimental stress-strain data. Various curve fitting methods are then employed to refine the parameters of the strain-hardening laws, enabling accurate representation of the steel rods mechanical behavior. Subsequently, these laws are implemented in Abaqus software for numerical simulation of uniaxial tensile tests, facilitating the analyses of material response under uniaxial tensile loading condition. Compared to the measured data, the predicted force-displacement curves are in good agreement with the measurements until the tail of the curves. The comparisons verify the ability and potential of the examined hardening law for studying the post-necking behavior of structural steels. The outcomes provide a framework for more precise characterization of structural steel materials.